Pengetahuan dan Perilaku Pelajar SMP dan SMA di Jawa Timur terhadap Protokol Kesehatan 6M - Natasha Vine Angelique; Syahrani Madiha Putri; Rika Putri Septiawati; Sagita Putri Ramadhina; Yussi Ananda; Syeila Rahmadina; Nadea Kalila Yasmin; Melisa Ramadhaniar; Hana Ameli Widyasari; Indiarto Lukman Susetiya; Dika Herian Saputra; Allisya Fathatul Fauziyah; Zenita Dwi Rahmaudina; Alfionita Isnaini; Elida Zairina (Fakultas Farmasi Universitas Setia Budi, 2023)
Since 2019, the infectious disease Covid-19 has spread throughout the world. Schools have begun to hold limited face-to-face meetings. This study sought to identify a knowledge profile and behavior profile of middle and high school students in East Java toward 6M health protocols, as well as the relationship between age, knowledge score, and practice score, as well as a comparison of knowledge and behavior profile based on gender, education level, and class. This study used a cross-sectional study with accidental sampling and questionnaires to collect data from 743 respondents in 8 districts or cities in East Java. The Spearman, Mann-Whitney, and Kruskal-Wallis tests were used for statistical analysis. The results show that 80,5% of respondents have good knowledge, and more than 90% had positive behavior towards 6M health protocols. There was a significant correlation between age and knowledge score (p<0,05), age and behavior score (p<0,05), and knowledge score and behavior score (p<0,05). The study also discovered differences in knowledge and behavior scores based on gender, education level, and class.